2016
DOI: 10.1016/j.nanoen.2015.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Nanowire/nanotube array tandem cells for overall solar neutral water splitting

Abstract: In this study, we report the fabrication and characterization of a novel PEC tandem cell, consisting of p-Si/TiO 2 /Fe 2 O 3 core/shell/hierarchical nanowire (csh-NW) array photocathode and TiO 2 /TiO 2 core/shell nanotube (cs-NT) array photoanode, for overall solar water splitting in a neutral pH water. The p-Si/n-TiO 2 /n-Fe 2 O 3 csh-NWs, made mainly by solution-processed methods, offer significantly improved performance in the neutral pH water with a low (positive) onset potential and photoactivity at zero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…overall ≥3 photoabsorbers), [21,22,57,123] its value compares favourably to stateof-the-art devices containing oxide-, [45,125] or single-junction silicon-photocathodes. [47,48,50,126] Moreover, the stability reaching 20 h and scalability of up to 10 cm 2 presented in this work counts among the highest reported values, even surpassing most PV-PEC and wired systems (see Table 2 for a detailed literature comparison), which emphasizes the relevance of our findings as an early step towards commercial implementation.…”
Section: Comparison With State-of-the-art and Outlooksupporting
confidence: 57%
See 1 more Smart Citation
“…overall ≥3 photoabsorbers), [21,22,57,123] its value compares favourably to stateof-the-art devices containing oxide-, [45,125] or single-junction silicon-photocathodes. [47,48,50,126] Moreover, the stability reaching 20 h and scalability of up to 10 cm 2 presented in this work counts among the highest reported values, even surpassing most PV-PEC and wired systems (see Table 2 for a detailed literature comparison), which emphasizes the relevance of our findings as an early step towards commercial implementation.…”
Section: Comparison With State-of-the-art and Outlooksupporting
confidence: 57%
“…In this case, the use of double-or multi-junction photovoltaics was ocasionally required to obtain an appropiate driving force for water splitting. [21,22,[36][37][38][39][40] In contrast, only a few photoelectrocatalytic tandems employing oxide, [41][42][43][44][45][46] or silicon [47][48][49][50] free conditions. For example, 0.6 V were required to reach a 0.11% applied bias solar-to-hydrogen (AB-STH) efficiency in Cu 2 O|NiO x -WO 3 tandems, [42] whereas a more optimized FTO|Au|Cu 2 O|Al:ZnO|TiO 2 |RuO x -BiVO 4 |Co-Pi system could later reach a bias-free photocurrent density of 0.32 mA cm −2 and a stability of 1.4 h. [45] Similarly, the combination of a siliconbased photocathode with a BiVO 4 |TiCo photoanode could achieve a maximal AB-STH efficiency of 0.59% at 0.6 V bias, [47] which was later improved to a bias-free value of 0.57% using a p-Si nanoarray|Pt-Mo:BiVO 4 |Co-Pi tandem.…”
Section: Introductionmentioning
confidence: 99%
“…The same trends as for the photo currents are also seen in the respective onset potentials (V onset ) for H 2 -evolution, here dened as the potential needed for reaching a net photocurrent density of À0.1 mA cm À2 . 53 A positive (anodic) shi of the onset potential (V onset ) was observed for the co-catalyst functionalized electrodes as compared to as-synthesized and p-Si/TiO 2 : the V onset of the control p-Si/TiO 2 sample was observed at À0.66 V RHE, whereas those for p-Si/TiO 2 /CoO x and p-Si/TiO 2 /NiO x were shied to +0.27 V RHE and +0.42 V RHE , respectively (ESI Table S1 †). The V onset value for our p-Si/TiO 2 /NiO x photoelectrode is remarkable when compared to a recent report by Zhang and coworkers, 33 where a V onset ¼ +0.25 V RHE (J ¼ À0.1 mA cm À2 ) was obtained for p-Si/NiCoSe x nanopillars in 0.5 M H 2 SO 4 where the concentration of protons is 10 6 times higher as compared to the neutral pH electrolyte employed here.…”
Section: Preparation and Structural Characterization Of Her Photoelecmentioning
confidence: 99%
“…Our results, instead, were obtained in a two-electrode configuration PECa cell without applying any bias between the electrodes ( V = 0). Kargar et al [58] reported an evaluation of PECa tandem cell performance using TiO 2 /TiO 2 core/shell nanotube array as photoanode for overall solar water splitting. They calculated a STH of 0.18% using AM 1.5 G filter, against 0.23% obtained with our PECa cell.…”
Section: Peca Efficiencymentioning
confidence: 99%